Screening brinjal genotypes for resistance to jassid (Amrasca biguttula biguttula [Ishida]) - Malini, C D; Prasanna, K P; Gopalakrishnan, T R (Journal of Tropical Agriculture, 2013)
An investigation was carried out in the Department of Olericulture, College of Horticulture, Kerala Agricultural University, Vellanikkara for screening brinjal genotypes for tolerance/ resistance to jassids. The accessions SM 363, SM 364, SM 366, SM 384 and SM 385 were found resistant to jassid infestation in the field screening as well as in artificial screening in cages. The morphological and anatomical bases of resistance were also unraveled. High midrib hair density and longer midrib hairs were found to impart resistance to jassids in the resistant accessions. Anatomical studies of midrib of susceptible and resistant accessions revealed variation in cuticle thickness, cell wall thickness of epidermal cells and intercellular space of hypodermal cells. These characters, either alone or in combination, may be contributing resistance to oviposition or feeding of jassids in brinjal .